Cloning, expression, and nucleotide sequence of a Staphylococcus aureus gene (fbpA) encoding a fibrinogen-binding protein. - Cheung, A I (1995)
Septicemia due to Staphylococcus aureus often begins as a focal infection (e.g., colonized wounds or catheters) from which the organism gains access to the bloodstream. On the basis of recent data from this laboratory, it is likely that S. aureus colonizes catheters and endothelium by using a fibrinogen-binding protein to mediate adhesion to fibrinogen-coated surfaces. To characterize the fibrinogen-reactive protein, we screened a lambda Zap library of S. aureus DB, a clinical isolate, for clones that were reactive with fibrinogen. Of 100,000 plaques screened, 3 were found to react with fibrinogen on immunoblots. Plasmid DNA prepared from clones 14, 30, and 36, upon digestion with EcoR1, which released the insert, revealed fragments of 4.6, 3.6, and 3.2 kb, respectively. To identify the cloned protein expressed in E. coli, cells were fractionated into periplasmic, membrane, and cytoplasmic fractions. Expression studies of clone 14, which comprised approximately two-thirds of the mature molecule, including the C terminus, revealed a 34-kDa fibrinogen-reactive protein in both the periplasmic and membrane fractions. This protein, designated FbpA, could be partially purified on a fibrinogen column. By using both clones 14 and 36 as templates, the complete DNA sequence of the fibrinogen-binding protein was obtained, yielding a molecule with a predicted size of 69,991 Da. Although sequence analysis revealed a high degree of homology with coagulase, there is a unique sequence of 11 amino acids that is not found in three known coagulases as well as two recently cloned fibrinogen-binding proteins. This unique sequence shares homology with a cell wall anchor motif found in other gram-positive surface proteins.